2019
DOI: 10.1093/humrep/dez188
|View full text |Cite
|
Sign up to set email alerts
|

Progression of deep infiltrating rectosigmoid endometriotic nodules

Abstract: STUDY QUESTION What is the risk of progression of deep endometriotic nodules infiltrating the rectosigmoid? SUMMARY ANSWER There is a risk of progression of deep endometriotic nodules infiltrating the rectosigmoid, particularly in menstruating women. WHAT IS KNOWN ALREADY Currently, there is a lack of acceptance in the literature on the probability that deepl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 27 publications
1
32
0
Order By: Relevance
“…However, medical therapy should be taken continuously, is contraceptive and may have side effects ( Vercellini et al , 2011 ). Expectant management may be followed by an increase in nodule size in 39% of cases after as little as 3 years ( Netter et al , 2019 ). For these reasons, surgical management may be considered to allow removal of endometriosis lesions and provide relief from symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…However, medical therapy should be taken continuously, is contraceptive and may have side effects ( Vercellini et al , 2011 ). Expectant management may be followed by an increase in nodule size in 39% of cases after as little as 3 years ( Netter et al , 2019 ). For these reasons, surgical management may be considered to allow removal of endometriosis lesions and provide relief from symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Progression of the disease and appearance of specific symptoms rarely occurs in patients with asymptomatic rectovaginal endometriosis 64 . However, progression of the disease occurs in some symptomatic patients 65 and to date, we do not know how to predict who will and will not progress 63 . Recent animal experiments showed that the stress-induced activation of hypothalamo-pituitary-adrenocortical (HPA) axis promoted the progression of endometriotic lesions 66,67 .…”
Section: Discussionmentioning
confidence: 99%
“…Netter et al [32] assessed rectosigmoid nodule measures variation in 43 women who underwent two MRIs at least 12 months apart. Nodule progression or regression was defined as, respectively, ³20% increase or ³20% decrease in length or in thickness.…”
Section: Rationale For Hormonal Treatment Of Bowel Endometriosismentioning
confidence: 99%
“…Barra et al [33] [32] reported persistence of pain symptoms in the vast majority of women in whom the nodule regressed or remained stable. On the other hand, Egekvist et al [29] observed that progression of nodule volume dimensions occurred without worsening of symptoms or healthrelated quality of life.…”
Section: Rationale For Hormonal Treatment Of Bowel Endometriosismentioning
confidence: 99%
See 1 more Smart Citation